Prevalent gastrointestinal nematodes of small ruminant raised in the Northwestern of Argentina (Veterinary Science, 2025)
The aim of this study was to describe the etiology and abundance of goat and sheep gastrointestinal nematodes (GIN) in different ecological regions of Northwest of Argentina (ANW). GIN was recovered from samples collected from necropsies carried out for different diagnostic cases (n= 117) from the following regions: chaqueña semi-arid, temperate valleys and humid forest, arid canyon and valleys and Puna of the provinces of Salta, Jujuy and Santiago del Estero. From abomasum and intestines samples GIN were recovered and counted. GIN species count differences were processed by non-parametric variance analysis and chi square. Recovered NGI and their respective prevalences were Haemonchus contortus (98,3%), Teladorsagia circumcincta (53,0%), Trichostrongylus axei (38,5%) Trichostrongylus colubriformis (85,5%), Trichuris spp. (41,9%), Oesophagostomum spp. (17,1%), Nematodirus spathiger (13,7%), Strongyloides papillosus (5,5%) and Cooperia curticei (1,1%). Burdens of H. contortus, T. colubriformis and total NGI recovered from the temperate valleys and humid forest ecoregions were higher (p
Keywords: Gastrointestinal nematodes; Goats; Sheep; Ecological regions; Northwest of Argentina